Clinical evaluation of NK-433 (centrally acting muscle relaxant, lanperisone hydrochloride) on temporomandibular joint arthrosis: I: Phase II Clinical Study - SATO, Koji; SHIRASU, Rikiya; OKA, Tohru; YOSHIZAWA, Nobuo; MURAKAMI, KenIchiro; SHIBATA, Takanori; IIZUKA, Tadahiko; AMAGASA, Teruo; OGAWA, Nobuya; ISHIBASHI, Katsunori; KAKUDO, Kenji; KINO, Koji (Journal of the Japanese Society for the Temporomandibular Joint, 1995)
A multicenter randomized comparative study was conducted in 189 patients with temporomandibular joint arthrosis (TMJ) to find the optimal dose regimen for NK-433 (a new centrally acting muscle relaxant). Patients were administered any one of doses of 50mg (50mg group), 100mg (100mg group), and 150mg (150mg group) of NK-433 for 2 weeks two times a day. (1) Out of 189 patients enrolled, the Final Global Improvement Rates (FGIR) were analyzed in 51 patients of the 50mg group, 54 patients of the 100mg group and 50 patients of the 150mg group. The Overall Safety Rate (OSR) was studied in 58 patients of the 50mg group, 64 patients of the 100mg group and 58 patients of the 150mg group. And the Final Global Usefulness Rates (FGUR) were analyzed in 53 patients of the 50mg group, 60 patients of the 100mg group and 53 patients of the 150mg group. (2) There was no siginificant difference among the 3 groups for “Moderate” and “Marked” improvement of FGIR, and the 150mg group was the highest rate with 74.0%. (3) Complaints were seen in 37 patients, but none of them was severe. (4) There was no siginificant difference among the 3 groups for “Usefulness” and “Very usefulness” of FGUR, and the 150mg group was the highest rate with 71.7%. In conclusion, NK-433 was shown to be useful in the treatment of TMJ arthrosis, and an optimal dose of 150mg a day was suggested.